WEB-BLOG IN TEACHING AND LEARNING READING COMPREHENSION AT INDONESIAN HIGHER EDUCATION (A CASE STUDY OF THE FOURTH SEMESTER STUDENTS’ OF MUHAMMADIYAH UNIVERSITY OF MAKASSAR) - Setiawan, A. Egi; Basri, Muhammad; Baa, Sultan (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This research aims at finding out the implementation of web-blog in teaching and learning Reading Comprehension at Indonesian higher education institution. The study specifically would like to discover: (1) The application of web-log in teaching Reading Comprehension in the classroom; and (2) the impact of web-blog application on the students’ Reading Comprehension skill. This research applied a qualitative descriptive method using observation checklist and interview to collect the data. Five (5) fourth semester students at the Muhammadiyah University of Makassar were selected as participants of the study using Purposive Random Sampling technique. The study found: (1) the lecturer perceived that the implementation of web-blog in teaching and learning reading comprehension skills has the potential to improve student learning outcomes, but technical problems and distractions are challenges that need to be overcome; and (2) the use of web- blog in teaching and learning Reading has a significant impact on increasing students' reading interest, motivation, and comprehension skills, making it an effective approach that offers a variety of benefits to students